(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This article analyzes antiseptic and disinfectant agents widely used in surgical practice. It provides detailed information on their chemical nature, mechanism of action against microorganisms, areas of application, advantages, and adverse effects. The article also highlights the principles of antisepsis and disinfection in modern medicine, as well as the distinctive features of next-generation antiseptics.